RULBI Multimedia for Contextual Math Learning in Grade V - Desak Ketut Rantris Priyatnis; Wiarta Wayan; Aditya Antara (International Journal of Elementary Education, 2025)
This study is a development research involving 29 students. The learning of multiplication and division faces challenges, with an average score of only 61.64, while the expected average is 80. Students encounter difficulties in multiplication and division, feel bored, and lack access to electronic media for learning these concepts at school. The objectives of this study are: (1) to design RULBI, (2) to assess the feasibility of RULBI, and (3) to evaluate the effectiveness of RULBI in teaching multiplication and division of whole numbers. Data were collected through tests and questionnaires, with quantitative descriptive, qualitative, and inferential statistical analysis. The RULBI design follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Expert evaluation of the design yielded a score of 89%, classified as good. Feasibility testing results were as follows: content expert validation (90%), instructional design expert (90%), media expert (91%), individual testing (89%), and small group testing (94.1%). The effectiveness test using a t-test showed tvalue = 8.41, while the ttable at a 5% significance level with degrees of freedom (df) = 28 was 1.701. Since the tvalue > ttable, H1 was accepted. The implication of this research is that RULBI is expected to have a positive impact on elementary education.